THE ISSUES OF ABSENTEEISM AND PRESENTEEISM IN TERMS OF THE RIGHT TO DECENT AND SAFE CONDITIONS OF LABOR - Bodnaruk, Mykola; Burka, Aliona (Visegrad Journal on Human Rights, 2023)
The right to work is a fundamental human right, whereas decent, safe and favorable conditions of labor are essential to its implementation. Today, decent labor implies efficient employment that provides a fair income, job security, and social protection. Approval of the concept of decent labor and its implementation in practice also means approval of the concept of respect for employees’ rights and taking measures to improve conditions of labor. The purpose of the study is to investigate the issues of absenteeism and presenteeism in terms of the right to decent and safe conditions of labor; to determine the interconnection between the improper fulfillment of the employer’s obligations to create a safe labor environment on the one hand, and absenteeism and presenteeism in the workplace on the other. The methodological basis of the research is the results of previously conducted foreign studies, scientific conclusions, and views on the concept, causes, consequences of absenteeism and presenteeism; legal acts and provisions of the International Labor Organization. The authors of the article emphasize that today’s labor activity carries more and more risks associated not only with the physical but also with the mental health of an employee. Therefore, modern safety and health management systems at enterprises, as well as legal norms, require constant transformation in the direction of the development of society, social values and employees’ needs. The article identifies the main causes of absenteeism, presenteeism and their consequences, as well as concludes that an unsafe labor environment is one of the main factors resulting in presenteeism and absenteeism. The article also points out that the implementation of certain programs (which aim at improving the balance between stress factors at work and work resources; supporting employees, taking care of their physical, mental, financial and social well-being; the formation of a safe, healthy, inclusive labor culture that increases productivity and work efficiency; the regulatory expansion of the content of the right to safe conditions of labor; the creation of additional guarantees for the employee in the field of occupational safety, in particular the safety of mental health and their consolidation at the local or legislative level) is now a necessity, a demand of society and a guarantee of the productive activity of enterprises and the growth of the economy as a whole.
Keywords: Absenteeism; Presenteeism; Occupational safety; Mental health; Labor